Sustainable House Cooling (SusHoC) System - HASNIZAM, SITI HASMALIZA; MOHD RIDZUAN, MUHAMMAD AMIR IRFAN; MUSA, MUHAMMAD NABIL FARID; MOHAMMAD, HAIRUDDIN (Multidisciplinary Applied Research and Innovation, 2026)
This proposal focuses on the development of a sustainable house cooling model designed to address the hot and humid climate of Malaysia, which often reduses the comfort of resdents and lowers indoor environmental quality. The research is driven by the need to reduce reliance on conventional cooling systems such as air conditioners, which are known to be energy-intensive and contribute to increased greehouse gas emissions. With growing awareness of climate change and its impacts, innovative and eco-friendly solutions are becoming increasingly important. The literature review in this study covers various types of houses in Malaysia, environmental challenges such as urban heat islands (UHI), and high humidity levels that affect thermal comfot and the health of residents. The reseach proposes a cooling system based on the concept of car radiaors as a more efficient and sustainable alternative. The methodology involves the design and development ofa house model using components such as radiators, water pumps, and transparent rubber pipes. Thissystem is tested to assess its effectiveness in reducing indoor temperature and humidity. The expected outcome is that this system will not only enhance the comfort of residents but also reduce energy comsumption and environmental impact, creating healthier and more sustainable living spaces. This research aims to encourage the adoptio of more eco-friendly and efficient cooling solutions in the future.